2014
DOI: 10.1186/1479-5868-11-78
|View full text |Cite
|
Sign up to set email alerts
|

A holistic school-based intervention for improving health-related knowledge, body composition, and fitness in elementary school students: an evaluation of the HealthMPowers program

Abstract: BackgroundOver the past 30 years, obesity in the United States has increased twofold in children and threefold in adolescents. In Georgia, nearly 17% of children aged 10 – 17 are obese. In response to the high prevalence of child obesity in Georgia and the potential deleterious consequences that this can have, HealthMPowers was founded in 1999 with the goal of preventing childhood obesity by improving health-enhancing behaviors in elementary schools, utilizing a holistic three-year program. This study measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 20 publications
4
45
0
5
Order By: Relevance
“…Nutrition and physical activity lessons were incorporated into the regular classroom curriculum. In fourth and fifth graders who were overweight or obese at the baseline measurement, BMI for age z‐score (see summary table) significantly decreased (p < .0001) . Three studies reported nonsignificant changes or no change in BMI percentiles …”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Nutrition and physical activity lessons were incorporated into the regular classroom curriculum. In fourth and fifth graders who were overweight or obese at the baseline measurement, BMI for age z‐score (see summary table) significantly decreased (p < .0001) . Three studies reported nonsignificant changes or no change in BMI percentiles …”
Section: Resultsmentioning
confidence: 98%
“…Table reports details of studies measuring the effect of nutrition education on BMI grades K‐5. In interventions that took place in schools attended by children in grades K‐5, 4 studies demonstrated a statistically significant decrease in the measured BMI percentile, primarily a decrease in the overweight/obese categories in the participants . Interventions of longer duration had more effect on students' BMI …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations